2021
DOI: 10.9767/bcrec.16.4.11895.888-903
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrogenation of Stearic Acid to 1-Octadecanol Using Bimetallic Palladium-Tin Supported on Carbon Catalysts at Mild Reaction Conditions

Abstract: Bimetallic palladium-tin catalysts supported on microporous carbon (denoted as Pd-Sn(x)/C, loading amount of Pd = 5 wt% and x = Pd/Sn molar ratio; c.a. 3.0; 1.5; and 1.0) showed high selectivity in the hydrogenation of stearic acid towards 1-octadecanol (stearyl alcohol) under mild reaction conditions. Pd-Sn(x)/C catalysts were synthesized via the hydrothermal method at temperature of 150 °C for 24 h, and reduced with H2 at 400 °C for 3 h. Pd-Sn(1.5)/C catalyst exhibited the highest yield of stearyl alcohol (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The change of electron density Ru enhanced the affinity of Ru towards C]O bond of fatty acids which facilitated the reaction hydrogenation. [30][31][32] Several bimetallic or alloy-based catalysts (e.g., Pd-M (M ¼ Cu, Co, Ni), 33 Ni-Sn/TiO 2 , 34 Pd-Nb 2 O 5 , 35 Ru-Sn, 31 Rh-Sn, 32 and Pd-Sn/C, 36 ) have shown superior performance for the selective hydrogenation of fatty acids compared with their single metal counterpart. Luo et al reported the hydrogenation of coconut oil to fatty alcohols using nanocluster Ru 3 Sn 7 /SiO 2 catalysts at 240 C, 40 bar.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The change of electron density Ru enhanced the affinity of Ru towards C]O bond of fatty acids which facilitated the reaction hydrogenation. [30][31][32] Several bimetallic or alloy-based catalysts (e.g., Pd-M (M ¼ Cu, Co, Ni), 33 Ni-Sn/TiO 2 , 34 Pd-Nb 2 O 5 , 35 Ru-Sn, 31 Rh-Sn, 32 and Pd-Sn/C, 36 ) have shown superior performance for the selective hydrogenation of fatty acids compared with their single metal counterpart. Luo et al reported the hydrogenation of coconut oil to fatty alcohols using nanocluster Ru 3 Sn 7 /SiO 2 catalysts at 240 C, 40 bar.…”
Section: Introductionmentioning
confidence: 99%
“…We have developed bimetallic catalysts (e.g., bimetallic Ni-Sn/TiO 2 , Pd-Fe/TiO 2 , Pd-Sn/C and Ru-Fe/TiO 2 catalysts) and showed high catalytic performances in the hydrogenation of typical biomass-derived levulinic acid to g-valerolactone, [54][55][56] lauric acid to dodecane-1-ol, 34,57 and stearic acid to octadecanol. 36 In the present paper, we describe our studies on the hydroconversion of lauric acid into lauryl alcohol using molybdenum oxide-modied ruthenium supported on titanium oxide (denoted as Ru-(y)MoO x /TiO 2 ; y ¼ loading amount of Mo, mmol g À1 ) catalysts. The addition of Mo ($0.026 mmol; Mo/Ru ¼ 0.5) to Ru/TiO 2 catalyst (denoted as Ru-(0.026)MoO x /TiO 2 ) greatly improved the hydrodeoxygenation of lauric acid and produced n-dodecane ($72% yield) at 190 C, 40 bar H 2 , and a reaction time of 7 h. An increase in reaction temperature to 200-230 C signicantly enhanced the degree of hydrodeoxygenation of lauric acid and yield of n-dodecane reached to maximum (80%) (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%